Effects of the Immunomodulatory Agent Cordyceps militaris on Airway Inflammation in a Mouse Asthma Model - Chia-Hsiu Hsu; Hai-Lun Sun; Ji-Nan Sheu; Min-Sho Ku; Chun-Ming Hu; You Chan; Ko-Huang Lue (Elsevier, 2008)
Cordyceps militaris is a well-known fungus with immunomodulatory activity. It is generally used in traditional Chinese medicine to treat hemoptysis, bronchial or lung inflammation, and urogenital disorders. The purpose of our study was to evaluate the effect of cultivated C. militaris on airway inflammation in a mouse asthma model. Methods: BALB/c mice were sensitized with intraperitoneal ovalbumin (OVA) on Days 0 and 14, and were then given intranasal OVA on Day 14 and Days 25-27. Randomized treatment groups of sensitized mice were administered C. militaris, prednisolone, montelukast, or placebo by gavage from Days 15-27. Airway hyperreactivity to aerosolized methacholine was determined. Bronchoalveolar lavage fluid and serum were analyzed to assess airway inflammation. Results: OVA-sensitized mice developed a significant airway inflammatory response that was inhibited by prednisolone and montelukast, whilst C. militaris reduced airway inflammation less effectively. Airway hyperresponsiveness to methacholine was observed in OVA-sensitized mice and was reversed by both prednisolone and montelukast. C. militaris initially reversed airway hyperreactivity, but this effect disappeared at higher methacholine doses. Conclusion: C. militaris can modulate airway inflammation in asthma, but it is less effective than prednisolone or montelukast. These results demonstrate that C. militaris is unable to adequately block the potent mediators of asthmatic airway inflammation.